2019
DOI: 10.1628/fa-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Are Excise Taxes on Beverages Fully Passed Through to Prices? The Danish Evidence

Abstract: This paper studies tax shifting of excise taxes on alcoholic and nonalcoholic beverages in Denmark. We use a unique data set collected by Statistics Denmark focusing on six episodes of tax changes: three tax cuts and three tax hikes. We find that excise taxes on beer and soda are overshifted but those on liquor are undershifted. We also find that the pass-through is inversely related to the size of the tax change and that there are asymmetric effects of tax changes on soda. Finally, the tax pass-through on bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 39 publications
5
26
1
5
Order By: Relevance
“…Gallus et al (2006: 118, Table 3) find an elasticity of -0.76 using European crosscountry data for 2000. The previous elasticity estimates are also consistent with the empirical evidence showing price over-shifting of specific taxation in the beverages and tobacco industries (Baker and Brechling, 1992, for wine in the UK; Besley and Rosen, 1999, for the US;Delipalla and O'Donnell, 2001, for the EU cigarettes market; Young and Bielinska-Kwapisz, 2002, for the US alcohol market; Bergman and Hansen, 2013, for the Danish beverage market; Bonnet and Réquillart, 2013, for the French soft drink market). It is worthy noticing that the partial equilibrium results of the current paper (Proposition 1) would remain qualitatively unaffected had one assumed a price inelastic demand in the range -0.5/-1.…”
Section: Discussing the Paper's Main Assumptions And Policy Implicationssupporting
confidence: 84%
See 1 more Smart Citation
“…Gallus et al (2006: 118, Table 3) find an elasticity of -0.76 using European crosscountry data for 2000. The previous elasticity estimates are also consistent with the empirical evidence showing price over-shifting of specific taxation in the beverages and tobacco industries (Baker and Brechling, 1992, for wine in the UK; Besley and Rosen, 1999, for the US;Delipalla and O'Donnell, 2001, for the EU cigarettes market; Young and Bielinska-Kwapisz, 2002, for the US alcohol market; Bergman and Hansen, 2013, for the Danish beverage market; Bonnet and Réquillart, 2013, for the French soft drink market). It is worthy noticing that the partial equilibrium results of the current paper (Proposition 1) would remain qualitatively unaffected had one assumed a price inelastic demand in the range -0.5/-1.…”
Section: Discussing the Paper's Main Assumptions And Policy Implicationssupporting
confidence: 84%
“…Regarding market structure and demands, the model assumptions of oligopolistic Cournot behaviour and integrated product markets seem broadly consistent with the existing empirical evidence for the EU alcohol (Bergman and Hansen, 2013) and tobacco markets (Delipalla and O'Donnell, 2001), in which however product differentiation also plays a role. The assumption of a unit-elastic product demand curve leading to tax over-shifting is also consistent with the empirical evidence for these industries.…”
Section: Discussing the Paper's Main Assumptions And Policy Implicationssupporting
confidence: 79%
“…These results for city-level taxes in the U.S. differ from estimates based on other countries, which tend to show pass-through rates above 100 percent (e.g.,Grogger, 2015;Berardi, Sevestre, Tepaut, & Vigneron, 2012;Bergman & Hansen, 2010). However, these country-level estimates are based on changes in prices over time in the taxed country and lack comparison groups.…”
mentioning
confidence: 99%
“…Denmark introduced a tax as a percentage of the price of soft drinks in 1998 and 2001 (Jensen and Smed 2013;Smed et al 2016). Bergman and Hansen (2016) analyzed a micro price data set and found that both tax increases were over-shifted on to consumers-that is, the price increase for consumers was higher than the nominal value of the tax.…”
Section: Impact Of Diet-related Taxesmentioning
confidence: 99%